Precision cuts time-comparative outcomes of laser hemorrhoidoplasty and open hemorrhoidectomy - Shreya,; Chandrashekar, Prajwal (International Surgery Journal, 2025)
Background: Hemorrhoidal disease, one of the most common anorectal disorders and significantly affects individuals’ quality of life and poses a considerable health burden globally. Persistent or advanced-grade hemorrhoids often require procedural interventions such as traditional surgical approaches but these are associated with significant risks and complications. Recent developments, including minimally invasive techniques like laser hemorrhoidoplasty, are transforming the treatment landscape. Methods: This research was a comparative, prospective study. It involved patients who were diagnosed to have grade II and III haemorrhoids with persistent symptoms. The patients were split into two groups: group 1, which underwent laser hemorrhoidoplasty, and group 2, which received open surgical haemorrhoidectomy and the mean age, duration of the surgery and antibiotic used were compared. Results: A total of 44 patients were included in the study. Group 1 consisted of 23 participants and group 2 consisted of 21 participants. The mean age between the two groups varied from 21 to 73 years and the mean difference was found to be 0.67. The mean duration of surgery in group 1 was found to be 30.87±14.11 whereas in group 2 it was found to be 96.43±48.09. The mean antibiotics used in group 1 was found to be 4.91±1.12 and in group 2 was found to be 7.81±2.84. Conclusions: Laser hemorrhoidoplasty is a safe, effective, and minimally invasive alternative to open hemorrhoidectomy for the management of symptomatic hemorrhoidal disease when compared to the duration of surgery, hospital stay and the perioperative antibiotic used.